Ketahanan Iman Kristen di Tengah Era Disrupsi - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2020)
Christian Faith Resilience Amidst the Era of Disruption. The current era of disruption which is marked by the birth of various innovations and new technologies cannot be avoided by all people, organizations and churches. The era of disruption will affect the Christian faith, so that the attitudes, policies and culture adopted by believers who are Christian to the influence caused by this era of disruption will greatly determine the continuity of their Christian faith, whether it will continue to grow or will die completely. With a descriptive qualitative method with a literature study approach, the author proposes a conceptual frame of the role of the challenge of Christian faith in the era of disruption. The main source of analysis includes research results contained in journals and books, which are analyzed by looking at the relationship and compatibility with the title of the writing. The results of this study on the era of disruption and dimensions of Christian faith are then used to formulate the concept of resilience of the Christian faith in the era of disruption. There are eight main attitudes that must be developed in order to maintain Christian faith in this era of disruption.